Development, standardization of polyherbal formulation of analgesic ointment of plant Carum copticum, Mentha piperita, Cedrus deodara - Sharma, Sharad; Sharma, Sonu; Pradhan, Pankaj; Pathak, Shailesh; Sharma, Monika (Creative Pharma Assent, 2020)
Ayurveda is one of the world’s oldest systems of medicine. It originated in India and has evolved there over thousands of years. The term “Ayurveda” combines then Sanskrit words ayur (life) andVeda (science or knowledge). Ayurveda means “the science of life. Medicinal plants and herbal drugs have played a key role in world health. According to world health organization (WHO), about 80% of the world population currently utilizes the herbal drugs. People are using herbal medicines from centuries for safety, efficacy, cultural acceptability, non-toxic, lesser side effects and easily available at affordable prices. In recent times, there has been a move in universal trend from synthetic to herbal medicine due to side effects of synthetic products. Herbal products may contain a single herb or combinations of several different herbs believed to have complementary and /synergistic effects. Some herbal products, including many traditional medicine formulations, also include animal products and minerals. Herbal products are sold as either raw plants or extracts of portions of the plant or in the form formulation i.e. tablet, capsule, syrup, cream and ointment etc. The different parts of plants with analgesic were taken up for the present study and investigated for the phytochemical screening and used for the formulation of analgesic ointment. Present study deals with formulation, Standardization, evaluation of ointment made from alcoholic extract and essential oil of different plants.